2022
DOI: 10.36628/ijhf.2022.0002
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Mortality Rate and Predictors of 30-Day Readmission in Patients With Heart Failure Exacerbation and Atrial Fibrillation: A Cross-Sectional Study

Abstract: Background and Objectives Heart failure (HF) and atrial fibrillation (AF) are considered new cardiovascular epidemics of the last decade. Recent national trends show an uptrend in HF hospitalizations. We aimed to identify the 30-day readmission rate, causes, and impact on healthcare utilization in HF exacerbation with a history of AF. Methods We utilized 2018 Nationwide readmission data and included patients aged ≥18 years with International Classification of Diseases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…There was evidence indicated that antiarrhythmic [ 28 , 29 ], beta-blockers [ 30 , 31 ], and anticoagulation [ 32 ] were correlated with the prognosis of patients with HF or patients with HF and AF. Charlson comorbidity index, the most extensively studied comorbidity index, was found to be associated with the clinical outcome in patients with HF [ 33 ] and an important predictor for 30-day readmission in patients with HF exacerbation and AF [ 34 ]. Age and creatinine were also demonstrated to have predictive value for in-hospital mortality in patients with cardiogenic shock [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was evidence indicated that antiarrhythmic [ 28 , 29 ], beta-blockers [ 30 , 31 ], and anticoagulation [ 32 ] were correlated with the prognosis of patients with HF or patients with HF and AF. Charlson comorbidity index, the most extensively studied comorbidity index, was found to be associated with the clinical outcome in patients with HF [ 33 ] and an important predictor for 30-day readmission in patients with HF exacerbation and AF [ 34 ]. Age and creatinine were also demonstrated to have predictive value for in-hospital mortality in patients with cardiogenic shock [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides invited review articles and guidelines, many research papers and review articles with various quality are submitted around the globe. Encouragingly, certain important papers published in IJHF have been highly cited, 2 3 4) which has been very pleasing to our contributing researchers. The accountability for and transparency in the quality of all published content lies with the editorial board of the IJHF .…”
mentioning
confidence: 92%
“…Furthermore, patients with heart failure are known to have a chronic course and a high rehospitalization rate. In the United States (U.S.), approximately 5 million patients have heart failure, and the readmission rate within 30 days of discharge is reported to be as high as 25% ( Heidenreich et al., 2013 ); furthermore, in 2018, the 30-day readmission rate was 16.7% ( Gangu et al., 2022 ). In China, the readmission rate within one month of discharge was the same ( Li, 2017 ).…”
Section: Introductionmentioning
confidence: 99%